2021
DOI: 10.1021/acs.jpclett.1c02574
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Quantum Vibrational Spectroscopy of Water with High-Order Path Integrals: From Bulk to Interfaces

Abstract: Vibrational spectroscopy is key in probing the interplay between the structure and dynamics of aqueous systems. To map different regions of experimental spectra to the microscopic structure of a system, it is important to combine them with first-principles atomistic simulations that incorporate the quantum nature of nuclei. Here we show that the large cost of calculating the quantum vibrational spectra of aqueous systems can be dramatically reduced compared with standard path integral methods by using approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…[38][39][40] Still, most of these methods exhibit an unfavorable scaling with system size. Second-generation potentials allow to address larger systems, and some vibrational studies for larger molecules, 41 clusters, 42 and condensed systems [43][44][45][46] have been reported. However, MLPs suitable for condensed systems have been typically constructed relying on density functional theory (DFT), which, although offering a good compromise between accuracy and efficiency for many systems, does not provide spectroscopic-quality vibrational frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Still, most of these methods exhibit an unfavorable scaling with system size. Second-generation potentials allow to address larger systems, and some vibrational studies for larger molecules, 41 clusters, 42 and condensed systems [43][44][45][46] have been reported. However, MLPs suitable for condensed systems have been typically constructed relying on density functional theory (DFT), which, although offering a good compromise between accuracy and efficiency for many systems, does not provide spectroscopic-quality vibrational frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…We further suspect that the obtained 𝜒 𝑦𝑦𝑧 (2) spectra (or 𝜒′ 𝑦𝑦𝑧 (2) spectra with the interfacial dielectric profiles for different water species) can be used for the critical check of the simulated spectra. 18,25,31,[37][38][39][40][41][42][43] It is more robust if one can see the agreement on not only the spectral lineshape but also the absolute amplitude of the spectra. 17,44 Such an attempt is on the horizon.…”
mentioning
confidence: 99%
“…Molecular dipole moment vectors have been trained directly by symmetry-adapted Gaussian process regression to accurately calculate the IR spectrum of liquid ambient water . Using the same approach, it was shown that the molecular polarizability tensor can also directly be trained which enables one to calculate machine learned Raman and SFG spectra from molecular dynamics simulations.…”
mentioning
confidence: 99%
“…Besides such equivariant message passing Neural Networks, also Gaussian process regression can be used to create equivariant machine learning models . This approach was utilized recently to train molecular dipole moment vectors and polarizability tensors. …”
mentioning
confidence: 99%
See 1 more Smart Citation